Persepsi Masyarakat Indonesia Terhadap Peran Apoteker Komunitas Dalam Promosi Dan Edukasi Kesehatan Berdasarkan Pekerjaan - Mahemba, Yunita Susanti; Soegiantoro, Didiek Hardiyanto; Rawar, Ellsya Angeline (Universitas Aufa Royhan, 2025)
Pharmacists play an important role in health promotion as part of disease prevention and quality of life improvement efforts. In their development, community pharmacists not only function as medicine providers, but also as health workers who provide education, counseling, and interprofessional collaboration. Public perception of this role still varies, so this study aims to analyze the Indonesian public's perception of the role of community pharmacists in health promotion and education based on job type. This study used a quantitative method with a cross-sectional design through an online questionnaire covering six dimensions of perception: general awareness, effectiveness, collaboration, barriers, trustworthiness, and health promotion and education. The sample size was determined using Cochran's formula at a 95% confidence level and a 10% margin of error, resulting in 100 respondents. The analysis was descriptive, using the Chi-Square test for the relationship between occupation and perception, as well as Spearman's correlation between perception variables. The results show that public perception ranges from fairly good to very good, with effectiveness (57%) and collaboration (55%) being the highest. The barriers variable shows a significant relationship with employment (p=0.044), while the other dimensions do not. Strong correlations are seen in general awareness, effectiveness, and collaboration. This study confirms the need to strengthen access to and consistency of health promotion services by community pharmacists.